2011
DOI: 10.1007/s00572-011-0404-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of endophytic and mycorrhizal fungi from seeds and roots of Dendrobium (Orchidaceae)

Abstract: The seed germination of orchids under natural conditions requires association with mycorrhizal fungi. Dendrobium nobile and Dendrobium chrysanthum are threatened orchid species in China where they are considered medicinal plants. For conservation and application of Dendrobium using symbiosis technology, we isolated culturable endophytic and mycorrhizal fungi colonized in the protocorms and adult roots of two species plants and identified them by morphological and molecular analyses (5.8S and nrLSU). Of the 127… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 34 publications
1
41
0
1
Order By: Relevance
“…Endophytic fungi, as mutualistic plant symbionts, Table S1). The present study corroborates previous works in the same field showing that there exists a rich endophyte assemblage in Dendrobium 14,[23][24][25][26][27] . The data revealed that the endophytic fungi population of D. officinale harboured a group of cosmopolitan species such as F. oxysporum, X. cubensis, Colletotrichum sp., Alternaria sp.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Endophytic fungi, as mutualistic plant symbionts, Table S1). The present study corroborates previous works in the same field showing that there exists a rich endophyte assemblage in Dendrobium 14,[23][24][25][26][27] . The data revealed that the endophytic fungi population of D. officinale harboured a group of cosmopolitan species such as F. oxysporum, X. cubensis, Colletotrichum sp., Alternaria sp.…”
Section: Discussionsupporting
confidence: 92%
“…The dominant endophytes in seven Dendrobium species from tropical regions of southwestern China were found to be Xylaria genus. The highest Xylaria species diversity and isolation rate of endophytes were achieved in D. nobile and D. chrysotoxum respectively 24,25 . A similar scenario was presented with Colletotrichum species which commonly isolated from plants in the tropics 35 .…”
Section: Discussionmentioning
confidence: 98%
“…Suppression of both bacteria and micromycetes was shown for root endophyte fungal species of Orchidaceae. They can also contribute to host plant fitness and successful establish ment of symbiotic relationships (Chen et al 2012, Zhao et al 2014. Another RAF species from G. repens roots, Verti cil lium leptobactrum, turned out to be active against plant pa tho genic nematodes and possesses a high biocontrol poten tial for agriculture (Hajji et al 2017).…”
Section: Discussion Fungal Partnersmentioning
confidence: 99%
“…Besides the mycobionts forming intracellular symbiotic interface within root cells, hyphal coils known as pelotons, orchids harbour a plethora of fungal root endophytes, sometimes referred as RAF (root-associated fungi), showing no specific intraradical structures (Bayman & Otero 2006, Kohout et al 2013. The interactions of such fungi with host plants are mostly unrevealed, but there are some reports on their plant-beneficial role due to ac ti vity against phytopathogenic microfungi and bacteria (Chen et al 2012, Zhao et al 2014. Another unique feature of orchid mycorrhiza is that despite of the complicated symbiotic contact zone and fine-tuned interactions between partners, there are no particular "orchid mycorrhizal fun gi" at all.…”
Section: A Mixotrophy Is In Question: New Data On Fungal Community Asmentioning
confidence: 99%
“…Although most (73%) the world's 17,000-35,000 orchid species exist as tropical epiphytes (Atwood 1986;Cribb et al 2003), surprisingly few taxa have been studied with respect to their mycorrhizal associations compared to their temperate terrestrial counterparts. During the last decade, however, a growing number of studies have been published that document mycorrhizal fungi from tropical orchids worldwide including Brazil (e.g., Pereira et al 2003Pereira et al , 2005, China (e.g., Chen et al 2012), Ecuador (Suárez et al 2006), Puerto Rico (Otero et al 2007), and Thailand (e.g., Nontachaiyapoom et al 2010) among other places. This information comes at a critical time for specialists seeking knowledge of mycorrhizal fungi for conservation purposes (e.g., symbiotic seed germination), but a great deal still must be learned about this aspect of orchid biology before effective protocols can be developed.…”
mentioning
confidence: 99%